Rendezvous with Rama - Clarke, Arthur C. (Arthur Charles), 1917-2008 (Mariner Books / Houghton Mifflin Harcourt, 2020)
"Winner of the Campbell, Hugo, Jupiter, and Nebula awards upon its release in 1973, Rendezvous with Rama is widely regarded as one of the cornerstones of Grand Master Arthur C. Clarke's work"--